Terapi Nutritif Modifikasi Modisco Menggunakan Ekstrak Nanas Meningkatkan Hemoglobin pada Tikus Wistar KEP Berat - Alfi Kamalia; Erma Sulistyaningsih; Sugiyanta Sugiyanta (Pustaka Kesehatan, 2014)
The data from the Health Research Association of Indonesian Ministry of Health in 2010 showed approximately 35.6% infants having PEM. The diet therapy for severe PEM is modisco. However, due to protein deficiency such as a protease enzyme resulting in nutrients malabsorption, modisco has not been able to compensate the lack of protein in PEM. It requires an active substance to increase protein absorption by adding a proteolytic enzyme. One of the source of proteolytic enzyme is pineapple. The study aimed to prove that addition of pineapple extract on modisco can increase levels of albumin and hemoglobin in severe PEM rats. This was a true experimental study with pre-post test control group design. The sample were 25 male Wistar rats aged 2 months. The data analysis using the Pairwise T test, one way ANOVA followed by LSD showed a significantly difference between pre and post test for both albumin and haemoglobin. The pineapple extract at a dose of 9 and 11 mg/day increased albumin level. And the dose of 7, 9 and 11 mg/day pineapple extract increase haemoglobin level. In conclusion, a modisco modification using pineapple extract for nutritive therapy increased both albumin and hemoglobin levels on severe MEP rats.   Keywords: Severe PEM, Modisco, Pineapple extract